Evidence and Experience, An Inevitable Pairing in Education (Journal of Parents and Teachers, 2025)
Evidence-based education proposes that pedagogical decisions be based on solid research, complemented by teaching experience and the school context. In contrast to myths and fads, this approach offers proven strategies such as feedback, spaced practice, and structured cooperative learning. Although it presents challenges, such as the gap between research and the classroom, it promotes equity, effectiveness, and professional development for teachers, consolidating a rigorous and reflective educational culture. In educational decision-making, research and experience are an inevitable pairing.
Keywords: evidence-based education; teaching strategies; student learning; educational practice; research utilization